MANAJEMEN BANDWIDTH DENGAN METODA HIERARCHIECAL TOKEN BUCKET BERBASIS MIKROTIK DAN MONITORING BANDWIDTH MENGGUNAKAN JAVA - Wahyudi Wahyudi (Jurnal PROCESSOR, 2015)
Bandwidth is one thing that is very important in a network. Bandwidth is the amount that shows how much data can be passed to a network connection. Along with the development of technology that will need more and more internet access as well as the available bandwidth, the greater bandwidth available then the better internet access is also available in a network.A lot of internet activity, such as downloading, playing online games or uploading would interfere with rapid access to the other client, it is necessary for a bandwidth management that every client get the same bandwidth.To optimize bandwidth management that is then needed a bandwidth monitoring application that will display the data in and data out of the computer.